Supporting the Health and Well-Being of Transgender Students - Cicero, Ethan C. (J Sch Nurs, 2017)
Throughout the United States, there has been a rise in public discourse about transgender people and transgender issues. Much of this attention stems from passed and proposed anti-LGBTQ (lesbian, gay, bisexual, transgender, queer or questioning) legislation, including “bathroom bills” that would require transgender people to use public facilities corresponding with the sex designated on their birth certificates. With the recent discussion and legislation impacting school-aged children and adolescents, what does this mean for school nurses and how can they care and advocate for their transgender students? In this article, we aim to empower school nurses to join the discussion, advocate for inclusive and equitable school policies, and deliver gender-affirming care to transgender students. We will explain transgender identities; transgender-related stigma, prejudice, discrimination, and health concerns; gender-affirming approaches in caring for transgender youth; and implications for school nurses. School nurses play a key role in creating a space that is welcoming and affirming where transgender students can thrive.